- #1

- 1

- 0

they take this equation ∑M

_{g}= I

_{G}∝ where ∝ = -a

_{gx}/r for the rotation of a rigid body where there is no slipping

They then change the equation to F⋅(h-r) = I

_{G}(-a

_{gx}/r)

why is ∑M

_{G}= F⋅(h-r) when ∝= -a

_{gx}/r

**?**

- Thread starter Parker Kary
- Start date

- #1

- 1

- 0

they take this equation ∑M

They then change the equation to F⋅(h-r) = I

why is ∑M

- #2

Stephen Tashi

Science Advisor

- 7,581

- 1,470

- Replies
- 6

- Views
- 2K

- Last Post

- Replies
- 2

- Views
- 1K

- Replies
- 5

- Views
- 2K

- Replies
- 3

- Views
- 2K

- Replies
- 18

- Views
- 2K

- Replies
- 4

- Views
- 5K

- Replies
- 8

- Views
- 2K

- Last Post

- Replies
- 6

- Views
- 2K

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 7

- Views
- 3K